Gambaran Kepatuhan Masyarakat Di Dusun Klengkungan Klaten Terhadap Protokol Kesehatan Covid-19 Post Vaccine - Trisnaningrum , Sekar; Dias Utami , Khirstina (HEALTHY BEHAVIOR JOURNAL, 2023)
Background: Covid-19 is considered as Public Health Emergency of International Concern (PHEIC). To deal with this issue, the government implemented Covid-19 vaccine program and encouraged society to do health protocol such as, using mask, washing hands, and social distancing.Method: The samples consisted of 96 respondents who had been vaccinated with 1st and 2nd doses, ranging from 17-45 years old.Result: The research results indicate that only 31.2% respondents who obeyed the three Covid-19 health protocol. It is revealed that most of the respondents who implemented the Covid-19 post vaccine protocol were female 17 (56.7%), ranging from age 17-25 were 12 respondents (40%), age 26-35 were 8 respondents (26.7%), age 36-46 were 10 respondents (33.3%) with SMA/SMK education were 15 respondents (50%).Conclusion: The majority of the characteristics of community respondents in Klengkungan hamlet are based on gender, the majority are male, namely 54.2% of respondents. The average age is 17-25 years as much as 41.7%. Respondent data by educational status is 59.4% SMA/SMK. The people in Klengkungan Hamlet are not obedient in wearing masks, namely with a percentage of 63.5%. The people in Klengkungan Hamlet are not obedient in washing their hands with a percentage of 65.6%. The people in Klengkungan Hamlet are not obedient in keeping their distance, namely with a percentage of 69.8%. The people in Klengkungan Hamlet are not compliant with the Covid-19 post vaccine health protocol, namely with a percentage of 68.8%.